COMPARATIVE EVALUATION OF PRELIMINARY PHARMACOGNOSY AND PHYTOCHEMISTRY OF TWO SOURCE PLANTS OF BALA (SIDA CORDIFOLIA, LINN. AND SIDA RETUSA LINN.) - V S, *Nimmy; Jayasreee, P.; Deepa, M. S (International Journal of Ayurveda and Pharma Research, 2017)
"Balaâ€- a predominant herbal drug, has wide selection of uses as a single drug and also is an ingredient in most of the popular and extensively used Ayurveda formulations. Ayurvedic Formulary of India accepts Sida cordifolia Linn. as Bala. Sida cordifolia being not so common in Southern parts of India has paved way for use of Sida retusa Linn., presently known as Sida alnifolia a common plant to be used as source plant of Bala in Kerala. In the present study, preliminary pharmacognostical, physical and phytochemical evaluation including chromatography of Sida cordifolia, Linn. and Sida retusa Linn. was done to evaluate their use as source plants of Bala. The pharmacognostical study by virtue of organoleptic evaluation and microscopy of Transverse section of the two species were performed and documented based on the standard procedure. The findings are valuable source of information as it may assist identification of the 2 drugs. Preliminary physical and phytochemical analysis of genuine sample of the study drug Sida cordifolia, Linn. and Sida retusa Linn. were conducted as a part of the study. These tests are simple and easy to carry out and give valuable information about the identity, genuineness and purity of the drug. The preliminary pharmacognostical and phytochemical screening of Sida cordifolia and Sida retusa suggests that either of the plants could be the source plants of Bala due to their immense similarity. It makes it highly probable that the pharmacological activities and therapeutic efficacy could possibly be same.